Iron deficiency in pulmonary arterial hypertension: prevalence and potential usefulness of oral supplementation. Issue 2 (4th March 2021) - Ghio, Stefano; Fortuni, Federico; Capettini, Anna Clizia; Scelsi, Laura; Greco, Alessandra; Vullo, Eleonora; Raineri, Claudia; Guida, Stefania; Turco, Annalisa; Gargiulo, Chiara; Oltrona Visconti, Luigi
Abstract: Background: The aim of this study was to evaluate the prevalence of iron depletion in a prevalent population of patients with pulmonary arterial hypertension (PAH) and to gain preliminary insights on the possibility of its treatment with oral drugs. Methods: Iron status was determined in 31 consecutive prevalent idiopathic patients with PAH. Iron depletion was defined as serum iron <10 mmol/L and decreased transferrin saturation irrespective of the coexistence of anaemia. Patients underwent laboratory examinations, 6-min walking test and echocardiography in the same day. A subgroup of iron depleted patients received one oral capsule/day containing 30 mg of pyrophosphate sucrosomial iron for 16 weeks. After this period all patients were re-evaluated. Results: Iron depletion was observed in 22 patients (71%), of whom 6 were also anaemic and 16 were not anaemic. Iron depletion was associated with higher systolic pulmonary artery pressure (60 [50–90] vs. 45 [40–50] mmHg, p  = .007), greater prevalence of moderate to severe tricuspid regurgitation (36% vs. 0%, p  = .039), lower tricuspid annular plane systolic excursion (23 [21–24] vs. 19 [18–20] mm; p  = .025]) and higher left ventricular eccentricity index (1.35 vs. 1, p  = .042). After 16 weeks of treatment, 6-min walking distance significantly improved (500 [390–500] vs. 530 [410–550] metres; p  = .043). Conclusions: Iron deficiency is highly prevalent in patients with PAH and is associated with worse clinical conditions. Treatment with oral sucrosomial iron is a therapeutic option which should be further investigated in future trials.